DIDACTIC APPROACH TO TECHNICAL TRANSLATION: COLLABORATIVE WORK AND PROJECT BASED LEARNING - Carabajal, Romina Valeria (2017)
The design of new methodological perspectives that combine different translation theories with the practice of translation is a difficult task in the area of translation didactics. The need to include changes in the teaching of specialized translation represents a challenge for teachers of Technical Translation of the English Public Translation graduate program at the School of Languages of Universidad Nacional del Comahue (Argentina). The methodological perspective applied to the translation of technical texts brings together different didactic strategies so as to modify the traditional methodology. This work aims at describing activities, focused on collaborative work and project-based learning, that students of Technical Translation carry out in order to foster autonomy in their own learning process with the teacher´s role as a facilitator of the process. It is believed that the application of this new methodology will provide students with the necessary abilities to perform their job appropriately in the labor market.